Assessing the Demand for Public Private Partnerships in Botswana’s Water Utilities Corporation: The Case of Lobatse Management Centre - Molokwane, T. (International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa, 2018)
The water authority in Botswana has been experiencing increasing challenges of water supply and distribution since the reform of the sector in 2009. The centralization of water supply and distribution on the Water Utilities Corporation stemming out of the implementation of the water sector reforms resulted in the prominence of water supply shortage in various parts of the country (both urban and rural) raising questions on government’s decision to reform the sector. The water supply service was previously provided by the Town and District Councils, The Department of Water Affairs and the Water Utilities Corporation. This paper investigates the possibility of engaging private companies through public private partnerships in the operations of the water service at Water Utilities Corporation’s Lobatse Management Center. The methodological approach of this study is mixed method approach. The research strategy adopted is a survey under an intrepretivist paradigm. The study’s findings illustrate that the corporation is overstretched in terms of its operational activities.The study’s findings also establish causes of water shortage as well as levels of (dis)satisfaction on service provided. The demand for engaging private companies is ascertained hence the need to consider the public private partnerships at the Lobatse Management Centre.
Journal article published in The 3rd Annual International Conference on Public Administration and Development Alternatives, 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Public Private Partnerships; Demand; Supply